A Study Of Shared Financial Services And Cash Management Practices By Corporate Sector In Malaysia - Chua, Kiew Chye (2005)
The cash management approaches by large Malaysian corporations has evolved and are already catching up and comparable with foreign multinational. The shared financial service is a concept whereby a business establishment consolidates its finance functions and provides in-house services in a particular location. This business model promises to save the companies business administration cost and also provide better services to the company's internal customers through streamlining processes and efficient delivery channels.